Exploring the structural determinants of novel xanthine derivatives as A2B adenosine receptor antagonists: a computational study. Issue 13 (2nd September 2019) - Yang, Yinfeng; Li, Yan; Zhou, Weiwei; Chen, Yaorong; Wu, Qian; Pan, Yanqiu; Zhang, Shuwei; Yang, Ling
Abstract: Adenosine is a ubiquitous endogenous nucleoside that controls numerous physiological functions via interacting with its specific G-coupled receptors. Activation of adenosine receptors (AdoRs), particularly A2B AdoRs promotes the release of inflammatory cytokines; reduces vascular permeabilization and induces angiogenesis, thereby making A2B AdoR becomes a potentially pharmacological target for drug development. Presently, for investigating the structural determinants of 164 xanthine derivatives as A2B AdoR antagonists, we performed an in silico study integrating with 3D-QSAR, docking and molecular dynamics (MD) simulation. The obtained optimal model shows strong predictability ( Q 2  = 0.647, R 2 ncv  = 0.955, and R 2 pred  = 0.848). Additionally, to explore the binding mode of the ligand with A2B AdoR and to understand their binding mechanism, docking analysis, MD simulations (20 ns), and the calculation of binding free energy were also carried out. Finally, the structural determinants of these xanthine derivatives were identified and a total of 20 novel A2B AdoR antagonists with improved potency were computationally designed, and their synthetic feasibility and selectivity were also evaluated. The information derived from the present study offers a better appreciation for exploring the interaction mechanism of the ligand with A2B AdoR, which could be helpful for designing novel potent A2B AdoR antagonists. Communicated by Ramaswamy H. Sarma